Implications of District Court Decisions on the Stages of the 2024 Elections: Perspectives on the Indonesian Election System - Inagatha Setyarahma Pangastuti; Radian Salman; Mohammad Syaiful Aris; Luh Putu Yeyen Karista Putri (PATTIMURA Legal Journal, 2025)
Introduction: The stipulation of Decision Number 757/Pdt.G/2022/PN.Jkt.Pst raises many pros and cons, namely related to the decision to postpone the 2024 elections. Through the Decision, the Central Jakarta District Court decided and adjudicated the Unlawful Acts dispute filed by the Adil Makmur People's Party against the General Election Commission. The Central Jakarta District Court should not have the authority to adjudicate disputes filed by the Adil Makmur People's Party because it violates absolute competence. Purposes of the Research: The purpose of this study is to analyze the position of the Decision and its legal consequences on the people's sovereignty in the electoral system in Indonesia. Methods of the Research: The research methods used are normative legal research methods, with a conceptual approach, a statue approach and a case approach. Results Main Findings of the Research: The research found that (1) the General Election Commission was right to appeal, showing that the 2024 election must be in accordance with the constitution, and (2) the postponement of the election violates the sovereignty of the people, as the election system in Indonesia should be carried out every five (5) years, and does not recognize the term postponing the election.